2010
DOI: 10.1089/acm.2009.0325
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Treatment Effectiveness, Medication Compliance, and Complementary and Alternative Medicine Use Among Veterans with Bipolar Disorder

Abstract: Prior research has suggested that persons who are dissatisfied with treatment for medical conditions are more likely to use CAM therapies. However, the results of this study do not show CAM therapies to be associated with perceived effectiveness of treatments for mental health problems among this sample of persons with serious mental illnesses. This suggests that motivations for CAM use may vary by population and condition. Because few correlates of CAM use among persons with serious mental illnesses are known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 19 publications
4
22
0
1
Order By: Relevance
“…In particular, most herbal medicines are OTC drugs; therefore, they can be used without a clinician's supervision. According to one previous study, most patients who use natural remedies do not reveal their use to their clinicians (Jarman et al, 2010). As such, clinicians need to ask their patients directly about the use of herbal medications and should be well-acquainted with their potential uses and common side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, most herbal medicines are OTC drugs; therefore, they can be used without a clinician's supervision. According to one previous study, most patients who use natural remedies do not reveal their use to their clinicians (Jarman et al, 2010). As such, clinicians need to ask their patients directly about the use of herbal medications and should be well-acquainted with their potential uses and common side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Eisenberg et al (2001) found that 41% of people who self-reported severe depression and 43% of those who reported anxiety had been using CAM in the previous year, a significantly higher rate than the 28% found in the overall sample. In subjects with bipolar disorder, about 40% have used CAM (Jarman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Gascon100 found that there was greater confidence in herbal or natural remedies than in prescription medicines to treat hypertension. Other research has found use of complementary and alternative medicine (CAM) to be associated with suboptimal medication-effectiveness beliefs129 and worse medication adherence 130134. Favorable attitude toward CAM has been reported to be associated with worse adherence intentions 135.…”
Section: Discussionmentioning
confidence: 99%
“…It was for this purpose that the eight-item scale was developed (Morisky Medication Adherence Scale ) and is now being used more as a research tool in the assessment of self-reported medication-taking behavior [1]. Recent research articles have used the MMAS-8 in different clinical settings assessing ulcerated colitis patients [2], hypertension [3], and complementary and alternative medicine [4].…”
mentioning
confidence: 99%